Perancangan Video Pembelajaran Sistem Kelistrikan Bodi Kendaraan Pada Mata Pelajaran Pemeliharaan Kelistrikan Kendaraan Ringan - zalman, alex sandra; basri, irma yulia; andrizal, andrizal; muslim, muslim (AEEJ : Journal of Automotive Engineering and Vocational Education, 2023)
The purpose of this research is to design instructional videos that will make learning easier for students. In this study the research and development (R&D) method was used and the subjects in this study consisted of material experts, media experts, and class XI students of Light Vehicle Engineering SMKN 1 West Sumatra. The data analysis technique of this research uses a quantitative descriptive technique, applies the results of product design in the form of learning video media, tests the level of validation and product feasibility on vehicle body electricity in light vehicle electricity subjects. Based on the results of the study, it can be concluded that the design of the learning video for the vehicle body electrical system in the light vehicle electrical maintenance subject is very suitable for use as a learning medium because it can be accessed anywhere and anytime and can be viewed repeatedly. Tujuan dari penelitian ini adalah untuk merancang video pembelajaran yang akan membuat belajar lebih mudah bagi siswa. Dalam penelitian ini digunakan metode research and development (R&D) dan subjek dalam penelitian ini terdiri dari ahli materi, ahli media, dan siswa kelas XI Teknik Kendaraan Ringan SMKN 1 Sumatera Barat. Teknik analisis data penelitian ini menggunakan teknik deskriptif kuantitatif, mengaplikasikan hasil perancangan produk dalam bentuk media video pembelajaran, menguji tingkat validasi dan kelayakan produk pada kelistrikan bodi kendaraan mata pelajaran kelistrikan kendaraan ringan. Berdasarkan hasil penelitian, maka dapat disimpulkan bahwa Perancangan video pembelajaran sistem kelistrikan bodi kendaraan pada mata pelajaran pemeliharaan kelistrikan kendaraan ringan ini sangat layak digunakan sebagai media pembelajaran karena dapat di akses dimanapun dan kapanpun dan bisa dilihat secara berulang-ulang.